Lipase‐Catalyzed Synthesis of Medium‐Long‐Medium Type Structured Lipids Using Tricaprylin and Trilinolenin as Substrate Models. (7th December 2012) - Bai, Shan; Aziz, Sarya; Khodadadi, Maryam; Bou Mitri, Christelle; St‐Louis, Richard; Kermasha, Selim
Abstract: The synthesis of medium‐long‐medium type structured lipids (SL) by the interesterification of tricaprylin (TC) and trilinolenin (TLN), using selected commercial lipases from Rhizomucor miehei (Lipozyme RM IM) and Candida antarctica (Novozym 435) was investigated. Although the bioconversion yield (BY) for Lipozyme RM IM (24.7 %) was close to that for Novozym 435 (24.0 %), the initial enzyme activity was 6.3 μmol CLnC/g enzyme/min and 1.6 μmol CLnC/g enzyme/min, respectively. Lipozyme RM IM was subsequently selected for further investigation. The structural analyses of SL indicated that the major products were 1, 3‐dicapryl‐2‐linolenyl glycerol (CLnC) and 1(3)‐capryl‐2, 3(1)‐dilinolenyl glycerol (CLnLn). In order to optimize the BY, selected parameters were investigated. The experimental results showed that using hexane as the reaction medium, at an initial water activity ( a w ) of 0.06, 10 mg solid enzyme/mL, substrate molar ratio of TC to TLN of 6:1 and a reaction time of 9 h, resulted in the highest BY (73.2 %). Using the optimized conditions, the effects of TLN concentration and other selective parameters, including the denaturation of the enzyme, controlling the a w and the addition of silica gel, on the mass productivity ( P M ), enzymatic productivity ( P E ) and volumetric productivity ( P V ) of the interesterification reaction, were also investigated.